Planning in the National Education System - Fauziah Habibilah; Wiwin Rahmawati; Hasbiyallah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Planning in the national education system is a strategic step to achieve high-quality, inclusive, and relevant education that meets the needs of society. This article discusses the basic concepts of educational planning, key elements in the planning process, as well as the challenges and opportunities faced during its implementation. Referring to national policies and international standards, educational planning must include needs analysis, resource allocation, curriculum development, and continuous evaluation. This article also highlights the importance of collaboration between the government, society, and the private sector in realizing an education system that is adaptive to changing times. This study aims to provide insights for the development of more targeted and sustainable education policies.